(untitled) (Journal of actual problems of jurisprudence, 2025)
This article studied the specificity of the legal system on the protection of children`s rights functioning in the Republic of Kazakhstan, attention is paid to the basic principles of international cooperation on problems of children. Protecting children as the national treasure, as well as the aspiration of the Republic of Kazakhstan to integrate into the world community has made this idea very relevant. The key purpose of the research is to identify the problems and gaps in the legal protection system for minors in the Republic of Kazakhstan and to provide recommendations to improve the existing practices taking into account the international best practices. It includes national legal regulations, international legal instruments, and practices of law enforcement in this area. As an academic work, this drugs a better understanding of legal processes for the protection of children rights and also to pin point existing legal gaps. The practical implications of its significance are seen in the recommendations made to amend national legislation to strengthen the protection of children’s rights. The research utilizes an eclectic method when analyzing legal regulations including international and domestic legislation, statistical analysis of the number of crimes against minors, as well as a review of the academic literature. The key findings indicate that there are still existing challenges in the development of the legal framework including the covert nature of crimes, weak cooperation between organs and inadequate legal protection of children’s property and information. The cross sectional data also reveals that the governmet has contributed to this by decreasing the rate children of even crimes though against the rate of serious crimes is still worrisome. The theoretical and practical significance of the research is shown in the recommendations made for the enhancement of the digital child protection as well as the incorporation of the principles of juvenile justice. The significance of the research is that it has the of potential being used in the development of a strategy that can be used in enhancing the protection of children’s rights and thus create a safe legal environment for children to grow and develop. Key words: child rights, global standards, juvenile justice system, UN guidelines on child rights, children’s digital security, social welfare protection.